IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI UPT SMPN 33 GRESIK - Yuhana, Lilis; Nursalim, Mochamad; Hazin, Mufarrihul; Khamidi, Amrozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) at UPT SMPN 33 Gresik based on Edward III's policy implementation theory, which includes four main elements: communication, resources, disposition, and bureaucratic structure. This research uses a qualitative approach with a case study method. Data were obtained through observation, in-depth interviews, and document studies, which were analyzed using Creswell's model. The results showed that the implementation of P5 in UPT SMPN 33 Gresik has gone well in the aspects of communication, disposition, and bureaucratic structure. Teachers and principals showed high enthusiasm and commitment in implementing P5, while systematic implementation procedures and project modules designed by the facilitator team became important guidelines in implementing the program. However, challenges were found in the resource aspect, such as limited supporting facilities for eco-print projects and the need for additional training for teachers, especially regarding project-based assessment. This study recommends increasing continuous training for teachers, procuring adequate supporting facilities, and strengthening collective reflection as part of ongoing evaluation. By paying attention to the four elements of Edward III's theory, the implementation of P5 is expected to run more optimally and have a significant impact on student character building according to the dimensions of the Pancasila Student Profile. Keywords: Pancasila Student Profile Strengthening Project, Edward III theory, policy implementation, Merdeka Curriculum, project-based learning